The media of diaspora - Karim, Karim H. (Karim Haiderali), 1956- (Transnationalism. Routledge research in transnationalism ;, 2003)
The Media of Diaspora examines how diasporic communities have used new communications media to maintain and develop community ties on a local and transnational level. This collection of essays from a wide range of different diasporic contexts is a unique contribution to the field.